APLIKASI ALTMAN’S Z-SCORE UNTUK MEMPREDIKSI KEPAILITAN PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2008-2017 - Andreas Anggara Anindyajati; Ika Yanuarti (Jurnal Bina Manajemen, 2018)
Altman’s Z-Score is a mathematical model consists of four to five financial variables’ that can be used by investor and company’s management to predict company’s bankruptcy. This study aims to find out how accurate the Altman Z”-Score in predicting bankruptcy of a company in Indonesia in the period 2008 until 2017. The result is Altman’s Z”-Score prediction is able to reach 75% with the total population of 32. The population in this research is divided into two groups, the first group is companies that go bankrupt and delisted from the Indonesia Stock Exchange named “class A”, the second group consist companies that are still listed in Exchange is named “class B”. A total of eight bankrupt companies are incorporated in class A, and class B becomes a “mirror” for class A that contains companies with similar characteristics. This research found that are some variables of Altman’s Z”-Score that can be used as early signs of company’s bankruptcy, that has negative values of retained earnings, cannot produce a positive EBIT, and have debt quite high. The author hopes the result of this study can be useful for investor to save their investment and company’s management in order to save the company and avoid bankruptcy.